Homogeneous distribution of Fe isotopes in the early solar nebula. (19th February 2013) - Wang, Kun; Moynier, Frédéric; Barrat, Jean‐Alix; Zanda, Brigitte; Paniello, Randal C.; Savage, Paul S.
Abstract To examine the iron (Fe) isotopic heterogeneities of CI and ordinary chondrites, we have analyzed several large chips (approximately 1 g) from three CI chondrites and three ordinary chondrites (LL5, L5, and H5). The Fe isotope compositions of five different samples of Orgueil, one from Ivuna and one from Alais (CI chondrites), are highly homogeneous. This new dataset provides a δ56Fe average of 0.02 ± 0.04‰ (2SE, n = 7), which represents the best available value for the Fe isotopic composition of CI chondrites and probably the best estimate of the bulk solar system. We conclude that the homogeneity of CI chondrites reflects the initial Fe isotopic homogeneity of the well‐mixed solar nebula. In contrast, larger (up to 0.26‰ in δ56Fe) isotopic variations have been found between separate approximately 1 g pieces of the same ordinary chondrite sample. The Fe isotope heterogeneities in ordinary chondrites appear to be controlled by the abundances of chondritic components, specifically chondrules, whose Fe isotope compositions have been fractionated by evaporation and recondensation during multiple heating events.